The Relationship Between Students' Perception of the Implementation of the Independent Curriculum and their Interest in Learning at Madrasah Aliyah East Jakarta - Talina Muqtashidah; Ahmad Sofyan (Asian Journal of Applied Education (AJAE), 2026)
This study aims to analyze the relationship between students’ perceptions of the implementation of the independent Curriculum and their learning interest at Madrasah Aliyah Jakarta Timur. This research employs a quantitative method with a correlational approach. Data were obtained from 108 students using a questionnaire that had been tested for validity and reliability. The results showed that students' perceptions of the Independent Curriculum had an average score of 120.51, with the highest score of 164 and the lowest score of 69, while students' learning interest had an average score of 72.78, with the highest score of 100 and the lowest score of 42. Spearman correlation analysis indicated a significant positive relationship between the two variables (r = 0.757, p < 0.01). Simple regression analiysis showed that students’ perceptions of the Independent Curriculum contributed 64% to learning interest, while 36% was influenced by other factors. The conclusion of this study is that the more positive students’ perceptions of the Independent Curriculum, the higher their learning interest.